Influence of external head cooling on the head, core body and blood temperatures using 3D whole-body model - Devarakonda, Surendra Balaji (Int J Numer Methods Heat Fluid Flow, 2018)
PURPOSE: The purpose of this study is to evaluate the impact of external head cooling on alleviating the heat stress in the human body by analyzing the temperatures of the core body (T(c)), blood (T(blood)) and head (T(h)) during exercise conditions using 3D whole body model. DESIGN/METHODOLOGY/APPROACH: Computational study is conducted to comprehend the influence of external head cooling on T(c), T(blood) and T(h). The Pennes bioheat and energy balance equations formulated for the whole-body model are solved concurrently to obtain T(c), T(blood) and T(h) for external head cooling values from 33 to 233 W/m(2) Increased external head cooling of 404 W/m(2) is used to compare the numerical and experimental Th data. FINDINGS: Significant reductions of 0.21°C and 0.38°C are observed in Th with external head cooling of 233 and 404 W/m(2), respectively. However, for external head cooling of 233 W/m(2), lesser reductions of 0.03°C and 0.06°C are found in T(c) and T(blood), respectively. Computational results for external head cooling of 404 W/m(2) show a difference of 15 per cent in T(h) compared to experimental values from literature. ORIGINALITY/VALUE: The development of stress because of heat generated within human body is major concern for athletes exercising at high intensities. This study provides an insight into the effectiveness of external head cooling in regulating the head and body temperatures during exercise conditions.